2015
DOI: 10.4236/abb.2015.69061
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Effect of Static Magnetic Fields on <i>C. elegans</i> Using Microfluidics

Abstract: In nature, several organisms possess a magnetic compass to navigate or migrate them to desired locations. It is thought that these organisms may use biogenic magnetic matter or light-sensitive photoreceptors to sense and orient themselves in magnetic fields. To unravel the underlying principles of magnetosensitivity and magnetoreception, previous experiments have been conducted on bacteria, vertebrates, crustaceans, and insects. In this study, the model organism, C. elegans, is used to test their response and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
12
1
Order By: Relevance
“…In nematology, the development of microfluidic assays have been primarily focused on the behavioral modeling of Caenorhabditis elegans (Saldanha et al 2013) and some parasites of veterinary importance (Chen et al 2011). These studies have also used image analysis combined with microfluidics to aid in data acquisition (Njus et al 2015;Saldanha et al 2013).…”
mentioning
confidence: 99%
“…In nematology, the development of microfluidic assays have been primarily focused on the behavioral modeling of Caenorhabditis elegans (Saldanha et al 2013) and some parasites of veterinary importance (Chen et al 2011). These studies have also used image analysis combined with microfluidics to aid in data acquisition (Njus et al 2015;Saldanha et al 2013).…”
mentioning
confidence: 99%
“…Not surprisingly, no test condition was significantly different from such a variable control. Therefore, in our view, the Njus et al (2015) study appears to offer little evidence to counter the idea that C. elegans orients to magnetic fields.…”
Section: New Behavioral Experiments Support Original Study Replicatiomentioning
confidence: 71%
“…Consistent with our original study that found that magnetic orientation required a cGMP-dependent signaling cascade including the cation channel TAX-4, Caldart and Golombek found that mutation of the TAX-4-obligate subunit TAX-2 abolished this migration (Fig 2B, p = 0.39, n = 12 in the presence of a magnet, p = 0.59, n = 12 when no magnet was present). Landler et al (2017) notes that a study by Njus et al (2015) reported that worms failed to respond to magnetic fields. Njus et al restricted their study to crawling velocity and omega bends and not orientation.…”
Section: New Behavioral Experiments Support Original Study Replicatiomentioning
confidence: 99%
“…For instance, this feature could be used for quantifying cell viability with spatial resolution within each well. It is worth noting that microplates with fewer wells (and consequently bigger ones) would allow experiments with small model animals such as C. elegans [25][26][27] and Planarians 18,28 where, we emphasize, the interpretation of any finding should take into careful consideration the nonnegligible field variations within each well.…”
Section: Discussionmentioning
confidence: 99%